Condensation in rod-like polyelectrolytes - the no-salt solution case (2013)
"The present thesis is the recompilation of several projects developed during the last three years in rod-like polyelectrolytes in the special no-salt case in the cell model. Our work presents contributions to the strong association regime in two and three dimensions as well as a measure of the condensation phenomenon at all levels. The models were contrasted against numerical results from Monte Carlo simulations. We obtained that Manning condensation in three dimensions is overestimated above the ideal value (1-1Ç) as a result of small box sizes and large couplings. For couplings beneath a threshold ([I] < 90), the condensation is that predicted by Manning. In two dimensions, the thermodynamic limit recovers the results for mean field. Conversely, with a finite number of counter-ions, the system undergoes a series of transitions corresponding to the binding of each individual charge; consequently, the strong coupling regime comes with full condensation. In both two and three dimensions the onset for condensation reads in terms of the Manning parameter as Ç = 1."